6.8k views
5 votes
E = 6c^2- 2c - 1 F = -4c^2 + 7c+ 5 E+F= Your answer should be a polynomial in standard form.

1 Answer

3 votes

Answer:


E+F=2c^2+5c+4

Step-by-step explanation: We have to find the E+F, given the following:


\begin{gathered} E=6c^2-2c-1 \\ F=-4c^2+7c+5 \end{gathered}

Then the answer simply is the addition of the two, which is done as follows:


\begin{gathered} E+F=(6c^2-2c-1+-4c^2)+(7c+5=2c^2+5c+4) \\ \therefore\rightarrow \\ E+F=2c^2+5c+4 \end{gathered}

User Akansh Tayal
by
5.6k points